2018
DOI: 10.1002/elan.201800602
|View full text |Cite
|
Sign up to set email alerts
|

Novel Calixarene/Carbon Nanotubes Based Screen Printed Sensors for Flow Injection Potentiometric Determination of Naproxen

Abstract: Novel sensitive disposable sensors have been introduced for potentiometric determination of naproxen (NAP) based on single‐walled carbon nanotubes‐polyvinyl chloride (SWNTs‐PVC) composite incorporated of calix[4]arene as host‐guest molecular recognition element. The electrode matrix composition was optimized on the basis of the nature and content of the sensing element, cationic sites, plasticizer and nanomaterial. Remarkable selectivity and sensitivity towards NAP was achieved in the concentration range from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…For example, Elmorsy et al developed novel disposable potentiometric sensors for detection of naproxen (NAP) that relied on single-walled carbon nanotubes-polyvinyl chloride (SWNTs-PVC) composite combined of calix [4]arene as host-guest molecular identification element 22 . The developed sensors have been applied for the assay of NAP with a fast response time and good stability reaches 24 weeks.…”
Section: Application Of the Potentiometric Sensors For The Determination Of Pharmaceutical Drugsmentioning
confidence: 99%
“…For example, Elmorsy et al developed novel disposable potentiometric sensors for detection of naproxen (NAP) that relied on single-walled carbon nanotubes-polyvinyl chloride (SWNTs-PVC) composite combined of calix [4]arene as host-guest molecular identification element 22 . The developed sensors have been applied for the assay of NAP with a fast response time and good stability reaches 24 weeks.…”
Section: Application Of the Potentiometric Sensors For The Determination Of Pharmaceutical Drugsmentioning
confidence: 99%
“…Super critical CO 2 medium was used as a novel approach for the decoration of MWCNTs with metal nanoparticles, the best results for vitamin B6 determination was achieved by using the SPE modified with RuNPs-MWCNTs, resulting in a minimum three-fold increase in sensitivity [ 274 ]. A nanocomposite based on MWCNTs-polyvinyl chloride and calixarene as a molecular recognition element have been used for SPE modification and applied for gentamicin potentiometric determination improving the stability, response time, lifetime, sensitivity and selectivity of the sensor [ 275 ]. Carboxylated MWCNTs decorated with AuNPs using ethylenediamine as a cross-linker were drop-casted on SPE and applied for electrochemical determination of amoxicillin combining the good electron transfer property and catalytic property of the two nanomaterials [ 276 ].…”
Section: Metal Nanoparticles and Carbon-based Nanomaterials In (Bio)sensors Designmentioning
confidence: 99%
“…During the years 2018-19, nine new methods using FIA-SPE systems were developed for the determination of analytes such as isoniazid, [60] arsenic, [61] salmonella bacteria, [62] o-diphenol and its derivatives, [63] ethoxyquin, [64] glucose, [65] naproxen, [66] three tumor biomarkers, [67] acetaminophen, [68] and tryptophan and pyridoxine simultaneously. [69] Oliveira et al [62] reported a simple, low-cost, and fully disposable microfluidic FIA device for ultrasensitive Salmonella bacteria detection.…”
Section: Spes Coupled To Fia Systemsmentioning
confidence: 99%